2022
DOI: 10.1111/ijau.12298
|View full text |Cite
|
Sign up to set email alerts
|

Government contracts and audit fees

Abstract: Topics concerning government contracts have recently attracted much attention from researchers and the public because of the US government's significant spending on goods and services. In this study, we investigate whether audit fees are associated with audit clients' government contracts. We find that firms with a higher proportion of government sales to total sales pay higher audit fees than other firms. Our further analysis shows the audit premium is driven mainly by the federal government and local governm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 69 publications
0
6
0
Order By: Relevance
“…Several recent studies have sought to link external auditing with government contracts (Dao et al, 2023;Hope et al, 2021). For instance, Hope et al (2021) use WBES data to report that firms that have their A result reported by Dao et al (2023) that is relevant to our study is the observation that firms with government contracts tend to pay higher audit fees compared to those without government contracts.…”
Section: The Effect Of Government Procurement and External Audit On A...mentioning
confidence: 99%
See 3 more Smart Citations
“…Several recent studies have sought to link external auditing with government contracts (Dao et al, 2023;Hope et al, 2021). For instance, Hope et al (2021) use WBES data to report that firms that have their A result reported by Dao et al (2023) that is relevant to our study is the observation that firms with government contracts tend to pay higher audit fees compared to those without government contracts.…”
Section: The Effect Of Government Procurement and External Audit On A...mentioning
confidence: 99%
“…However, the evidence is inconclusive, and some authors have recently called for research that explores the correlation between audit choices and other firm characteristics (Dedman et al, 2014;Lisowsky & Minnis, 2020). Thus, our third contribution relates to recent studies that have linked government procurement contracts with external audit certifications (Dao et al, 2023;Hope et al, 2021). These studies demonstrate that government monitoring incentives influence external audit certification (Hope et al, 2021) and that firms with government procurement contracts, when compared to those without, pay higher audit fees (Dao et al, 2023).…”
Section: Introductionmentioning
confidence: 96%
See 2 more Smart Citations
“…Company (Size) is an important factor that affects audit fees. This study measures a company's year-end total assets on a logarithmic scale, following existing research (Dao et al, 2022). Larger companies generally have more complex business operations, which imply higher potential risks.…”
Section: Control Variablementioning
confidence: 99%